Ovisidal dan Vermisidal Bawang Putih terhadap Telur dan Cacing Ascaridia galli pada Ayam Kampung (OVICIDAL AND VERMICIDAL ACTIVITIES OF GARLIC AGAINST THE EGGS AND ADULT HELMINTH OF ASCARIDIA GALLI IN KAMPONG CHICKENS) - Oka, Ida Bagus Made (Jurnal Veteriner, 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: garlic; A. galli; kampong chickens